2015
DOI: 10.1007/s12032-015-0671-2
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 is required for BLyS-mediated NF-κB signaling in multiple myeloma cells

Abstract: Tumor necrosis factor receptor-associated factor 6 (TRAF6) transduces signals from members of the IL-1R/TLR and TNFR superfamilies to the transcription factors NF-κB and AP1. Elevated expression of the TNF family member B-lymphocyte stimulator (BLyS) in multiple myeloma (MM) has been described recently. However, the precise process by which BLyS signals in myeloma cell remains unknown. Here, we identified increased expression of TRAF6 in MM patient cells and the MM cell lines U266, RPMI8226, and KM3. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The underlying mechanism was subsequently explored. It is found that TRAF6 is highly expressed in myeloma cells and known to regulate the downstream NF-κB signaling pathways and participates in the proliferation and apoptosis of myeloma cells [26]. NF-κB is a pivotal regulator of the immune system and is involved in a variety of neoplastic diseases, which is known to be involved in IL-17A stimulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism was subsequently explored. It is found that TRAF6 is highly expressed in myeloma cells and known to regulate the downstream NF-κB signaling pathways and participates in the proliferation and apoptosis of myeloma cells [26]. NF-κB is a pivotal regulator of the immune system and is involved in a variety of neoplastic diseases, which is known to be involved in IL-17A stimulation [27].…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib may be of more interest among the various therapeutic options in patients with AHA in the course of MM. Bortezomib has a directly cytotoxic effect on neoplasmatic plasma cells through the inhibition of the proteasome/nuclear factor-kappa B (NF-B) axis which is essential for interaction with the myeloma environment [57,58]. Furthermore, bortezomib has been described as an ISS drug efficient in SLE [59] and myasthenia gravis [60].…”
Section: Inhibitor Eradicationmentioning
confidence: 99%